Rereading Middle English romance : manuscript layout, decoration, and the rhetoric of composite structure - Evans, Murray J. (Murray James), 1949- (CEL - Canadian Publishers Collection., 1995)
With reference to features of layout and decoration, Evans interprets Guy of Warwick as a composite work, not separate works as some scholars suggest. Examining Sir Isumbras as a homiletic romance, and Sir Degaré and Sir Orfeo as Middle English lays, he shows how different versions of these romances, in their varied composite manuscript contexts, necessitate different readings of the "same" works and of their subgenres. Evans considers the manuscript structure of groups of works with different authorship and establishes six models of composite literary structure for Middle English literature. Evans argues that manuscript groupings of romances - and of romances with nonromances - enrich our interpretations of individual romances, romance as a genre, and medieval literary structure. This original study will appeal to readers interested in medieval romance and manuscripts, medieval literary structure, and computer applications in the humanities.